Wave 1 findings from Journeys Home: A longitudinal study of factors affecting housing stability - Scutella, R; Johnson, G; Moschion, J; Tseng, Y; Wooden, M (My University, 2013)
As part of the National Homelessness Research Agenda, the Australian Government commissioned The Melbourne Institute of Applied Economic and Social Research to undertake Journeys Home, a large-scale national longitudinal study of Australians drawn from a broad sample of Australian income-support recipients who are either homeless or vulnerable to homelessness. In this paper we present key findings from the first wave of the Journeys Home study, which was conducted over the period September to November 2011. Our aims are threefold. First, we wish to establish key differences in the demographic profiles of the JH sample with that of the general population. Second, we examine respondents’ experiences of homelessness, by estimating the incidence of homelessness at the time of interview and by examining homeless histories. Third, we examine the relationship between particular risk factors commonly associated with homelessness and respondents actual homeless experiences.
Keywords: Life Events -- Impact; Housing; Surveys and Survey Methodology; Surveys and Survey Methodology; Disadvantage, adversity and resilience; Surveys and survey methodology; Housing, communities and neighbourhoods; Life Events; Housing; Surveys and Survey Methodology; Impact; Adversity and resilience; Surveys and Survey Methodology; Dsiadvantage, adversity and resilience; Housing, communities and neighbourhoods